Malaysian Chinese and their influence on China-Malaysia relations: A contemporary perspective - Borges, D.; Costa, C. M. (Frontiers in Political Science, 2025)
Malaysian Chinese have been an essential part of Malaysian society for centuries, playing a key economic role and being an active party in Malaysian politics. Throughout most of their existence, these groups have also managed to stay connected with China through the bamboo network, a string of connections that China has sought to revitalize in the last decades. This paper explores the impact of Malaysia-Chinese on China-Malaysia relations, demonstrating how these groups have profoundly shaped these relations. The study revolves around three essential factors governing the Malaysian Chinese and their interactions within this framework. First, we explore the internal dynamics of the relationship between Malaysian Chinese groups and their host societies, notably driven by ethnic tensions and economic development. Second, we analyze China's initiatives toward connecting with Malaysian Chinese groups, evaluating their scope and motivations. Third, we scrutinize contemporary Sino-Malaysian relations and key interaction points that Malaysian Chinese groups have highly impacted. This analysis contributes to a generally understudied relationship between Chinese ethnicity and foreign policy in Southeast Asia, whose impact has deeply marked the state's strategies and foreign policies.